Thermo-optical performance of a solar funnel cooker - Carrillo-Andrés, Antonio; Apaolaza-Pagoaga, Xabier; Serrano-Casares, Francisco Víctor; Domínguez-Muñoz, Fernando (My University, 2020)
Funnel type solar cookers are simple, effective and have multiple advantages in practical use, but there is limited data available in scientific literature about their thermo-optical performance. This work aims to fill this lack of data. A well known model of solar funnel cooker has been subject to a series of experimental tests, indoor and outdoor, using different working fluids (water and oil). The experimental data has been used to calibrate the parameters of a simple thermal model. The calibrated model predictions show good agreement with experimental data and figures of merit describing the thermo-optical performance of the cooker are provided.
Keywords: Energía solar; Análisis termico; Solar; Solar funnel cooker; Experimentation; Thermal mode; Figure of merit